2010
DOI: 10.1007/s11748-009-0535-9
|View full text |Cite
|
Sign up to set email alerts
|

Endobronchial fibroleiomyomatous hamartoma: a diagnostic pitfall

Abstract: A 46 year-old man was found to have a polypoidal growth in the lumen of the right main bronchus. Fiberoptic bronchoscope-guided biopsy of the mass on two occasions showed acute-on-chronic inflammation. The origin of the polyp was the right upper lobe bronchus; and upper lobectomy with adequate resection margin was done. Histopathology examination of the polyp showed features compatible with benign fibroleiomyomatous hamartoma. True fibroleiomyomatous hamartoma arising primarily in the lung is rare and presents… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
4
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 9 publications
1
4
0
1
Order By: Relevance
“…Indeed, in a review of 215 cases of pulmonary hamartomas reported, only one case similar to our cases was found . To our knowledge, seven tumors, which were characterized by histopathologic appearances of a well‐circumscribed single nodule composing only of smooth‐muscle cells and columnar epithelial cells without cartilage and fat tissue, have been found in the English literature . Different diagnostic terms including adenofibroma, adenomyomatous hamartoma, and fibroleiomyomatous hamartoma have been applied to them.…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…Indeed, in a review of 215 cases of pulmonary hamartomas reported, only one case similar to our cases was found . To our knowledge, seven tumors, which were characterized by histopathologic appearances of a well‐circumscribed single nodule composing only of smooth‐muscle cells and columnar epithelial cells without cartilage and fat tissue, have been found in the English literature . Different diagnostic terms including adenofibroma, adenomyomatous hamartoma, and fibroleiomyomatous hamartoma have been applied to them.…”
Section: Discussionsupporting
confidence: 63%
“…2 To our knowledge, seven tumors, which were characterized by histopathologic appearances of a well-circumscribed single nodule composing only of smooth-muscle cells and columnar epithelial cells without cartilage and fat tissue, have been found in the English literature. 2,7,8,10,[12][13][14][15][16] Different diagnostic terms including adenofibroma, adenomyomatous hamartoma, and fibroleiomyomatous hamartoma have been applied to them. The clinicopathological features of the reported cases have been summarized ( Table 2).…”
Section: Discussionmentioning
confidence: 99%
“…In our case, the bronchial epithelium extended into the alveolar septa in the pulmonary parenchyma without a cartilaginous or adipose element. the lesion may be solitary or multiple in single or double lung, may occur in any part of the lung parenchyma, even occur in the bronchus with polypoid blocking of the bronchial lumen [4]. Three cases reported in this group had single and multiple, all occurred in the lung parenchyma.…”
Section: Discussionmentioning
confidence: 64%
“…Genellikle histopatolojik olarak tanı zorluğu olmamakla birlikte nadir histolojik varyantlar (fibroleiomyomatöz vb.) tanı karışıklığına neden olabilir (18). Olgularımızda baskın olan histopatolojik özellik kondroid tipte olup tanı zorluğu yaratan histolojik varyant izlenmemiştir.…”
Section: Introductionunclassified